Survival Analysis On The Reproductive And Production Performances Of Dairy Cow In Bogor - Brian Rinaldy Irsyad; Bagus Priyo Purwanto; Epi Taufik (Pusat Publikasi Nusantara, 2023)
The aim of this study was to analyze the reproductive performance (empty period) and production (peak time of milk production) of 87 dairy cows (Friesian Holstein) at X dairy farm Bogor using survival analysis. The analysis results based on the Kaplan-Meier curve showed that the median total idle time, primiparous cow, multiparous cow, cow that gave birth in the rainy and dry seasons were 210; 335; 231; 272; and 397 days. The median value of the total peak milk production, primiparous cow, multiparous cow, cow that give birth in the rainy and dry seasons is 41; 41; 39; 41; 41 days. The Cox Proportional Hazard regression results on idle time showed that the multiparous cow was 1.84 times more likely (P<0.05) to have a shorter idle period than the primiparous cow. Cows that gave birth during the rainy season had a 1.80 times shorter chance than cows that gave birth during the dry season, although they were not statistically significantly different (P=0.043). The regression results on peak milk production showed no difference between cows and primiparous cows. Meanwhile, cows that gave birth during the rainy season experienced peak lactation 1.26 times and tended to be faster than cows that gave birth during the dry season, although this was not statistically significant. The study's conclusions show that it was necessary to improve the management of reproduction and production of X dairy farm in Bogor.